STRATEGI PEMULIHAN EKONOMI MELALUI INOVASI OLAHAN KETAN SUSU PREMIUM MELALUI WIRAUSAHA MERDEKA UNIVERSITAS MUHAMMADIYAH SURAKARTA - Rizal Fathur Rizqy; Feri Setyowibowo (Prosiding Seminar Nasional Indonesia, 2025)
An area can be said to be ask if it can to build the economic problems of the community. In the current era, young people tend to be attracted to an independent style to meet their life needs. Many students are looking for side jobs to fill their free time or to earn extra income while studying. This can be overcome by the solution that will be provided, namely an economic recovery strategy through innovation product of premium sticky rice through independent entrepreneurs. This assistance is carried out with the aim of providing opportunities for students to innovate in student economic recovery strategies. The method  uses become the Asset Based Community Development (ABCD) approach. The expect to results here are to be able to provide innovation for students for economic recovery, additional income for students.